Strategic knowledge, IT capabilities and innovation ambidexterity: role of business process performance - Yogesh Dwivedi (Industrial Management and Data Systems, 2023)
Purpose: The research aims to identify the impacts of strategic knowledge (SK) and information technology capabilities (ITC) on innovation ambidexterity (IAM) through business process performance (BPP). Design/methodology/approach: The research framework is developed based on the theoretical grounding of resource orchestration (RO) (SK and ITC) impacts on IAM. The structural equation modeling (SEM) technique was used to test the research framework on a sample of 441 responses from Brazilian firms. Findings: The results suggest that SK and ITC facilitate BPP, resulting in IAM. The findings also suggested differences in path coefficients in the SK and ITC of the business value generation process framework under environmental turbulence (ET). Finally, a strong SK of ITC is especially important in enabling BPP and IAM in large firms. Another case of most manufacturing and service firms demonstrated that both SK and ITC are essential to impacting IAM through BPP mediation. Practical implications: The findings provide insight into how professionals can think and plan carefully to align SK and ITC for achieving balanced innovation and improving BPP in the dynamic business environment. Originality/value: The study establishes a relationship between SK, ITC, BPP and IAM. The study developed novel constructs of SK and ITC and tested them, which gives new insight and links among the constructs.